The investigation of Muslim male behavior during ablution: the introduction of ablution tub design guideline / Nor Haliza Johari - Johari, Nor Haliza (2014)
The research is based on the investigation of Muslim male behavior during ablution and the existing design of ablution station (ablution tub). Ablution is part of compulsory ritual of washing process to cleanse oneself from small impurities. The ablution ritual is a spiritual washing for all Muslims before performing the prayers and this ritual has been recorded in the Holy Quran. Based on previous research, the ablution process normally requires about six to nine litres of water, however about only half to two liters of water is enough to be applied on the compulsory body parts. Since, this ritual involves the use of water, the Muslims introduced ablution station in the mosque for the congregation to perform the ablution. Based on the observation in this study, the ablution tub design has many design variations based on its geography, ethnography and sociology. From these variations, it also symbiotic with behavior that influences the way people performs the ablution ritual significantly. Behavioral differences affected the efficiency of water usage that led to water wastage. A survey at Masjid Sultan Salahuddin Abdul Aziz Shah (MSSAAS), Shah Alam, Selangor Darul Ehsan, Malaysia was conduct on the ablution ritual among Muslim male congregation. From the survey, the correlation between human behaviour and the consumption of water during ablution ritual was determined to be the design of ablution tub. The existing design does not help the Muslim male to perform ablution ritual in efficient manner. Through the design study approach, the existing ablution design tub was enhanced. These enhancements manage to control the human behavior and the usage of water was reducing significantly. Finally, symbiotic between ablution ritual and the enhanced ablution tub design was successfully established.